Improved maternity care if midwives learn to perform ultrasound: a qualitative study of Rwandan midwives' experiences and views of obstetric ultrasound - Sophia Holmlund; Joseph Ntaganira; Kristina Edvardsson; Pham Thi Lan; Jean Paul Semasaka Sengoma; Annika Åhman; Rhonda Small; Ingrid Mogren (Taylor & Francis Group, 2017)
Background: Obstetric ultrasound has become an indispensable part of antenatal care worldwide. Although the use of ultrasound has shown benefits in the reduction of maternal and foetal morbidity and mortality, it has also raised many ethical challenges. Because of insufficient numbers of midwives in Rwanda, uncomplicated pregnancy care is usually provided by nurses in local health centres. Obstetric ultrasound is generally performed by physicians at higher levels of healthcare, where midwives are also more likely to be employed. Objectives: To explore Rwandan midwives' experiences and views of the role of obstetric ultrasound in relation to clinical management, including ethical aspects. Methods: A qualitative study design was employed. Six focus group discussions were held in 2015 with 23 midwives working in maternity care in rural and urban areas of Rwanda, as part of the CROss Country Ultrasound Study (CROCUS). Results: Obstetric ultrasound was experienced as playing a very important role in clinical management of pregnant women, but participants emphasised that it should not overshadow other clinical examinations. The unequal distribution of ultrasound services throughout Rwanda was considered a challenge, and access was described as low, especially in rural areas. To increase the quality of maternity care, some advocated strongly for midwives to be trained in ultrasound and for physicians to receive additional training. In general, pregnant women were perceived both as requesting more ultrasound examinations than they received, and as not being satisfied with an antenatal consultation if ultrasound was not performed. Conclusions: Obstetric ultrasound plays a significant role in maternity care in Rwanda. Increasing demand for ultrasound examinations from pregnant women needs to be balanced with medical indication and health benefits. Training of midwives to perform obstetric ultrasound and further training for physicians would help to address access to ultrasound for greater numbers of women across Rwanda. RESPONSIBLE EDITOR Virgilio Mariano Salazar Torres, Karolinska Institute, Sweden